Loss of CCAAT‐enhancer‐binding protein alpha (CEBPA) is linked to poor prognosis in PTEN deleted and TMPRSS2:ERG fusion type prostate cancers. Issue 3 (14th November 2018) - Minner, Sarah; Lutz, Jannes; Hube‐Magg, Claudia; Kluth, Martina; Simon, Ronald; Höflmayer, Doris; Burandt, Eike; Tsourlakis, Maria Christina; Sauter, Guido; Büscheck, Franziska; Wilczak, Waldemar; Steurer, Stefan; et al.
Abstract : Background: The transcription factor CCAAT‐enhancer‐binding protein alpha (CEBPA) is a crucial regulator of cell proliferation and differentiation. Expression levels of CEBPA have been suggested to be prognostic in various tumor types. Methods: Here, we analyzed the immunohistochemical expression of CEBPA in a tissue microarray containing more than 17 000 prostate cancer specimens with annotated clinical and molecular data including for example TMPRSS2:ERG fusion and PTEN deletion status. Results: Normal prostate glands showed moderate to strong CEBPA staining, while CEBPA expression was frequently reduced (40%) or lost (30%) in prostate cancers. Absence of detectable CEBPA expression was markedly more frequent in ERG negative (45%) as compared to ERG positive cancers (20%, P < 0.0001). Reduced CEBPA expression was linked to unfavorable phenotype ( P < 0.0001) and poor prognosis ( P = 0.0008). Subgroup analyses revealed, that the prognostic value of CEBPA loss was entirely driven by tumors carrying both TMPRSS2:ERG fusions and PTEN deletions. In this subgroup, CEBPA loss was tightly linked to advanced tumor stage ( P < 0.0001), high Gleason grade ( P < 0.0001), positive nodal stage (0.0003), and early biochemical recurrence ( P = 0.0007), while these associations were absent or markedly diminished in tumors with normal PTEN copy numbers and/or absence of ERG fusion. Conclusions: CEBPA is down regulated in about one third of prostate cancers, but the clinical impact of CEBPA loss is strictly limited to the subset of about 10% prostate cancers carrying both ERG fusion and deletions of the PTEN tumor suppressor. Our findings challenge the concept that prognostic molecular markers may be generally applicable to all prostate cancers.